Gender Differences in Communication Styles Among Santri At Pesantren Al Hikam Burneh, Bangkalan - Amalia Hasan; Zulkhaeriyah Zulkhaeriyah; Bima Kurniawan; Diah Silviana (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates how male and female santri at Pesantren Al Hikam Burneh differ in their communication styles, guided by Deborah Tannen’s (1991) theory of rapport talk and report talk. The research seeks to answer how gender influences language use in both private and public interactions within the pesantren environment. Using a qualitative descriptive method, data were collected through interviews with several male and female santri who actively engage in daily communication. The findings show that female santri tend to express empathy, support, and emotional openness, which align with rapport talk, while male santri often focus on clarity and giving solutions, reflecting report talk. However, the results also reveal differences from Tannen’s assumptions; female santri appear more confident in public speaking, and male santri show politeness and restraint influenced by pesantren values. These variations suggest that gendered communication among santri is shaped not only by gender roles but also by religious and cultural norms that promote respect, balance, and harmony.